Effects of froth properties on dewatering of flotation products– A critical review. (15th August 2020) - Zhang, Na; Chen, Xumeng; Peng, Yongjun
Highlights: Tenacious froth negatively affects dewatering, which is related to its structure. Froth structure is affected by particle properties, water quality and clay minerals. Froth rheology illustrates the particle-bubble interactions in froth structure. Stable froth prevents particles from settling while increasing final cake moisture. Controlling froth interfacial properties will increase the dewatering efficiency. Abstract: The presence of tenacious froth in flotation products has a detrimental effect on the downstream dewatering process, which is a challenge in processing plants of a range of commodities, such as coal, talc, molybdenum, bitumen, potash, zinc, copper and gold. The generation of tenacious froth is not only related to the properties of mineral particles but can also be affected by water salinity and the presence of clay minerals. In this article, the effects of stable froth on the dewatering of flotation products were presented. Froth properties including froth structure, froth stability and froth rheology were presented first and then recent studies on the influence of froth on dewatering process were reviewed. Finally, future directions of research to increase the dewatering efficiency of flotation products are recommended.